VD_FINDINFO Décision / 2020 / 189 vom 6. Februar 2020 - VD Tribunal cantonal (2020)
CLASSEMENT DE LA PROCÉDURE, FRAIS DE LA PROCÉDURE, JUGE UNIQUE, INDEMNITÉEN GÉNÉRAL | 319 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 al. 1 let. a CPP (CH)